1983
DOI: 10.1007/bf02019476
|View full text |Cite
|
Sign up to set email alerts
|

A new selective medium for the isolation ofCampylobacter jejuni from human faeces

Abstract: A new selective medium, Butzler's medium Virion, for the isolation of Campylobacter jejuni from human faeces is described. This medium contains the following antibiotics per liter: cefoperazone 15 mg, rifampicin 10 mg, colistin 10,000 IU, and amphotericin B 2 mg. At 42 degrees C there was no difference in the isolation rate on Butzler's medium Virion and Butzler's medium Oxoid, but the competing faecal flora was best suppressed by the new medium which allows easier reading of plates and better recognition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…All media were from bioMerieux (Marcy l'Etoile, France). Thermophilic campylobacters were sought on Butzler medium Virion [7] incubated for 2 days at 42°C in a microaerobic atmosphere (Don Whitley jar with H2 + CO2 gas generating kit without catalyst). Conventional identification techniques were used.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…All media were from bioMerieux (Marcy l'Etoile, France). Thermophilic campylobacters were sought on Butzler medium Virion [7] incubated for 2 days at 42°C in a microaerobic atmosphere (Don Whitley jar with H2 + CO2 gas generating kit without catalyst). Conventional identification techniques were used.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Reliable isolation methods for the bacteriological examination of such cases have been developed (Skirrow, 1977;Goossens et al, 1983), and by means of these methods it has been shown that in developed countries C. jejuni is responsible for about 5 to 10~o of cases of human enteric disease (Bruce et al, 1977;Severin, 1978;Steele and McDermott, 1978;Blaser et al, 1979). …”
Section: Introductionmentioning
confidence: 98%
“…A single colony was randomly selected from the Preston plate and incubated in a Preston enrichment broth for 48 h at 42 'C. A sample from the broth was then plated for confluent growth onto four blood agar plates containing FBP supplement (Goossens et al 1984), incubated as above, and subjected to hippurate hydrolysis and nalidixic acid susceptibility tests, using the methods of Skirrow & Benjamin (1983). The purity of the cultures was checked by a Gram stain and 10,l of the culture was then placed in each of two FBP glycerol vials and retained for subsequent serogrouping (see below).…”
Section: Introductionmentioning
confidence: 99%